Diminished expression of CD40 ligand by activated neonatal T cells. - Nonoyama, S (1995)
CD40 and CD40 ligand (gp39) mediate contact-dependent T-B cell interaction. We determined the expression of CD40 ligand by activated neonatal T cells and the response of neonatal B cells when activated through CD40. Although expression of CD40 ligand peaked simultaneously in both activated adult and neonatal cells, neonatal T cells expressed significantly less CD40 ligand surface protein and mRNA than adult T cells. Activated thymocytes also expressed far less CD40 ligand than adult T cells. Consistent with these results, activated neonatal T cells exhibited less helper function than activated adult T cells. Neonatal T cells primed and restimulated in vitro expressed CD40 ligand in amounts comparable with adult T cells and provided B cell help more effectively. This suggests that the poor expression of CD40 ligand reflects antigenic naiveté rather than an intrinsic defect of neonatal T cells. Neonatal B cells cultured with soluble CD40 ligand (sgp39) and IL-10 produced IgM in amounts comparable with adult cells, but much less IgG and IgA. Nevertheless, neonatal B cells were capable of proliferation and class switching, since sgp39 and IL-4 induced proliferation and IgE production comparable to adult B cells and production of modest amounts of IgG. Together, these results indicate that diminished CD40 ligand expression, along with decreased production of lymphokines, may be responsible, at least in part, for the transient immunodeficiency observed in human neonates.